On the trace elements contained in the volcanic ashes erupted from Mt. Sakurajima and the other volcanos - TAKESHITA, Toshio; NAGATA, Saneaki; MAEDA, Shigeru (Journal of Japan Society of Air Pollution, 1980)
The falling volcanic ashes erupted from Mt. Sakurajima, Mt. Aso, and Mt. Usu were assayed on trace elements. The mixtures of the ashes and rain were collected every month from April 1979 through Mar. 1980 at six locations in Sakurajima. The amounts of the falling volcanic ashes, and the contents of water-soluble component, SO42-, and in the filtrate of the mixture were measured. The data obtained were compared with those of the year before:(1) the amount of the ashes decreased;(2) the contents of the water-soluble component, SO42-, and Cl-increased;(3) pH of the filtrate lowered. The above results suggested that the ashes were somewhat worse this period with respect to environmental pollution. The another investigation on the falling ashes of Mt. Sakurajima, Mt. Aso, and Mt. Usu which had been out of contact with rain gave the following results;(1) the ashes of Mt. Sakurajima had the largest mean grain size, and that of Mt. Usu had the smallest mean grain size;(2) Mt. Aso was the highest in the content of the watersoluble component and SO42-;(3) heavy-metal content of the ashes of Mt. Usu was remarkably higher than those of Mt. Sakurajima and Mt. Aso;(4) phthalic acid esters had been to some degree adsorbed on the individual ashes: the ashes of Mt. Usu contained 241 ppm of DBP and 143 ppm of DOP.